2001
DOI: 10.17487/rfc3161
|View full text |Cite
|
Sign up to set email alerts
|

Internet X.509 Public Key Infrastructure Time-Stamp Protocol (TSP)

Abstract: Status of this Memo This document specifies an Internet standards track protocol for the Internet community, and requests discussion and suggestions for improvements. Please refer to the current edition of the "Internet Official Protocol Standards" (STD 1) for the standardization state and status of this protocol. Distribution of this memo is unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 0 publications
0
96
0
7
Order By: Relevance
“…An attacker could modify the logs and then re-hash and re-sign all the blocks starting from the earliest modified one, as the signing keys would be available on the log collector host. A cryptographic time-stamping service [2] could be used as a mitigation. Note that a time-stamp generally only provides evidence of the time and integrity of the time-stamped datum, but not the identity of the requesting party, so a time-stamp alone would not be sufficient to prevent a log file from another system being submitted instead of the original one.…”
Section: General Technical Considerationsmentioning
confidence: 99%
“…An attacker could modify the logs and then re-hash and re-sign all the blocks starting from the earliest modified one, as the signing keys would be available on the log collector host. A cryptographic time-stamping service [2] could be used as a mitigation. Note that a time-stamp generally only provides evidence of the time and integrity of the time-stamped datum, but not the identity of the requesting party, so a time-stamp alone would not be sufficient to prevent a log file from another system being submitted instead of the original one.…”
Section: General Technical Considerationsmentioning
confidence: 99%
“…The electronic data with the time stamp is made at the time stamp bureau, by uniting time information with the hash value of the data (Adams et al, 2001). In the verification of the data falsification, it can be confirmed that the data existed at the time indicated with the time stamp and data is not falsified after that by comparing former data with the hash value of data with the time stamp.…”
Section: The Time Stampmentioning
confidence: 99%
“…Hence, we developed and released the Web service called "The existence proof service of the Web pages" that create the Web cache and adds the time stamp (Adams et al, 2001) as the grounds that the cache has not been changed. It can be proven that the Web page had existed on URL at the certain past time and that the content of cache has not been changed, with this Web service.…”
Section: Introductionmentioning
confidence: 99%
“…This field contains the timestamp in UTF-8 format YYYYMMDDHHMMSSZ, where YYYY is the year (0000 -9999), MM is the numerical value of the month (01 -12), DD is the day of the month (01 -31), HH is the hour of the day (00 -23), MM is the minute within the hour (00 -59), SS is the seconds within the minute (00 -59), and the letter Z indicates that this is Zulu time. This format is loosely based on [RFC3161].…”
Section: -+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+mentioning
confidence: 99%